2009
DOI: 10.3802/jgo.2009.20.4.221
|View full text |Cite
|
Sign up to set email alerts
|

Weekly cisplatin or gemcitabine concomitant with radiation in the management of locally advanced carcinoma cervix: results from an observational study

Abstract: Objective: The use of non-platinum drugs in concurrent chemoradiation in carcinoma cervix has not been well explored and hence a two arm study was planned to compare the outcome of concomitant cisplatin or gemcitabine in locally advanced carcinoma cervix. Methods: Thirty six patients were evaluated in this study for response rates and complications. These patients were divided into two arms, sixteen patients in the cisplatin arm and twenty patients in the gemcitabine arm. Cisplatin and gemcitabine were given a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 16 publications
(23 reference statements)
2
10
0
Order By: Relevance
“…Probably low economic condition resulting in poor general condition of cervical cancer patients in our country is the cause of high incidence of anemia and other haematological toxicities met in the present study. Grade 2 dermatitis was more in cisplatin group 16% vs. 12% in gemcitabine group and is similar to the study done by Arun k et al (15) . Grade 3 toxicity was not seen in our study as evident in study by Bhatt et al (9) .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Probably low economic condition resulting in poor general condition of cervical cancer patients in our country is the cause of high incidence of anemia and other haematological toxicities met in the present study. Grade 2 dermatitis was more in cisplatin group 16% vs. 12% in gemcitabine group and is similar to the study done by Arun k et al (15) . Grade 3 toxicity was not seen in our study as evident in study by Bhatt et al (9) .…”
Section: Discussionsupporting
confidence: 90%
“…Grade 1 thrombocytopenia was seen in 8% and 4% patients in group A and group B respectively in our study. This was comparable with the study by Arun K et al (15) in which grade 1 thrombocytopenia was 2/20 vs 0/16 in gemcitabine and cisplatine arm respectively. Probably low economic condition resulting in poor general condition of cervical cancer patients in our country is the cause of high incidence of anemia and other haematological toxicities met in the present study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Phase I study with docetaxel as a radiation sensitizer has been reported. 7 Verma et al 4 reported the results from observational study between weekly cisplatin and weekly gemcitabin during radiation therapy with equal disease control rate and tolerable toxicity profile. In his review, results from combined cisplatin and gemcitabin with radiation were thoroughly reviewed in discussion.…”
mentioning
confidence: 99%
“…In this issue of Journal of Gynecology Oncology, there are 3 articles dealing with cervical cancer either with locally advanced tumor or with metastatic nodes at paraaortic region found at the time of operation. [3][4][5] Radiation has been the primary treatment modality for locally advanced cervical cancer (FIGO stage IB2-IVA). Weekly cisplatin is a standard one as a concurrent chemo-radiotherapy with improved local control and survival.…”
mentioning
confidence: 99%